2015
DOI: 10.20286/nova-jmbs-040156
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Brucellosis among High Risk Groups in Northern State, Sudan

Abstract: Aim this study was to determine the prevalence of brucellosis in various occupations in Northern State, Sudan, during 2012. A total of 753 serum samples (from 21 veterinarian, 39 meat inspectors, 407 abattoir workers and 286 animal handlers) in different localities were collected and screened for brucella antibodies by using Rose Bengal Plate Test (RBPT), Serum Agglutination Test (SAT) and 2 Mercaptoethanol Test(2MET). Then information's of occupation, age, sex, kind of work were recorded. Seroprevalence of br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…However, it is higher than many reports from different parts of the country which were between 0.3% and 6.0% [ 13 , 14 , 20 - 24 ]. On the other hand, it is lower than a report from the northern part of Sudan which was 16.3% [ 25 ].…”
Section: Discussioncontrasting
confidence: 65%
“…However, it is higher than many reports from different parts of the country which were between 0.3% and 6.0% [ 13 , 14 , 20 - 24 ]. On the other hand, it is lower than a report from the northern part of Sudan which was 16.3% [ 25 ].…”
Section: Discussioncontrasting
confidence: 65%
“…Since majority of butchermen are males who has high risk of acquiring brucellosis, it can be the reasons for the high prevalence of the disease. This is similar to findings by other studies [32, 33]. However, none of these have establish the risk that shepherds have towards brucellosis in Tanzania despite the fact that they are at the starting point of the livestock value chain.…”
Section: Discussionsupporting
confidence: 88%
“…The difference can be attributed to differences in geographical locations and the use of a single but highly sensitive test (Rapid agglutination test) in the previous study. In other parts of Africa, brucellosis studies among high risk occupations in Ghana and Nigeria in slaughterhouses found seroprevalences of 9.6% [25] and 24.1% [11] while a study in Sudan found varying prevalences of 9.5%, 15.3%, 24.4% and 26.5% among veterinarians, meat inspectors, abattoir workers and animal handlers, respectively [26]. The findings in Ghana, Nigeria and Sudan were higher than those found in this study in all occupational groups.…”
Section: Discussionmentioning
confidence: 99%
“…[15] A recent study carried out in Sudan reported a seroprevalence of 9.5%, 15.3%, 24.4% and 26.5% in veterinarians, meat inspectors, abattoir workers and animal handlers respectively. [16] A seroprevalence of 40% among high-risk groups has also reported in Libya. [17] In West Africa, Nigeria confirmed endemicity of bovine brucellosis among slaughtered cattle using the ELISA, showing that it is an occupational hazard to workers directly involved in cattle meat processing.…”
Section: Introductionmentioning
confidence: 98%